Pengaruh Tingkat Hunian Kamar dan Pendapatan Spa terhadap Laba Operasional di Nusa Dua Beach Hotel & Spa - I Putu Arnawa (JURNAL BISNIS HOSPITALITI, 2020)
The purpose of this research is to determine the effect of room occupancy and spa revenue on operating profit at Nusa Dua Beach Hotel & Spa. The data analysis technique used was descriptive quantitative, and analyzed with the test of classical regression assumption, analysis multiple linear regression, individual parameter significance test (t test), simultaneous significance test (Test F) and coefficient of determination R2. Report of room occupancy, spa revenue and operating profit at Nusa Dua Beach Hotel & Spa period 2017 to 2019. The results of this research indicate that the room occupancy and spa revenue have a positive and significant effect on operating profit with the regression equation Y = -484,794,904,574 + 28,760,823,190X1 + 3,260X2 and determination coefficient is 70,2%. Room occupancy and spa revenue partially and simultaneously have a significant effect on operating profit at Nusa Dua Beach Hotel & Spa.